Ed Ricketts and Tony Jackson - Ed Ricketts, Junior:::Creator::::::::::::
Ed 'Doc' Ricketts and Toni Jackson climbing ramp of the Princes Maquinna. Jackson lived with Ed Ricketts for seven years. The location is listed on back as being near Kildonan Cannery.